2016
DOI: 10.1515/jpem-2015-0470
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of idiopathic intracranial hypertension and associated factors in obese children and adolescents

Abstract: In childhood obesity, IIH should be kept in mind as a serious complication. Funduscopic examination is an easy method that suggests IIH. In particular, obese children with systemic hypertension and refractory headache should be considered for IIH.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 42 publications
1
9
2
Order By: Relevance
“…In our study population, the percentage of subjects with an abnormal carbohydrate metabolism is (of unknown reasons) lower compared to, e.g., that of the Swedish childhood obesity treatment registry BORIS showing a prevalence of 17.1% [5]. In contrast to other studies, the prevalence of hypertension in our study population is high [23,24]. This can be explained by the high percentage of obese and extremely obese patients, and the use of KiGGS reference values for definition of hypertension [25].…”
Section: Discussioncontrasting
confidence: 59%
“…In our study population, the percentage of subjects with an abnormal carbohydrate metabolism is (of unknown reasons) lower compared to, e.g., that of the Swedish childhood obesity treatment registry BORIS showing a prevalence of 17.1% [5]. In contrast to other studies, the prevalence of hypertension in our study population is high [23,24]. This can be explained by the high percentage of obese and extremely obese patients, and the use of KiGGS reference values for definition of hypertension [25].…”
Section: Discussioncontrasting
confidence: 59%
“…Moreover, complaints of headache, blurred vision and vomiting were significantly higher in subjects with IIH compared to other subjects. In this study, insulin resistance, dyslipidemia and hepatosteatosis were found to be more prevalent with IIH than the others [11]. Our patient's abnormal blood tests that could suggest a developing metabolic syndrome, with TGO and TGP levels higher than normal, hypertension, but lipid-line investigation did not identify dyslipidemia.…”
Section: A B Discussioncontrasting
confidence: 43%
“…In contrast, a study of obese children and adolescents found that those identified with pseudotumor cerebri syndrome (1.32%) had significantly higher morning cortisol levels. 30 Hormonal changes in children with pseudotumor cerebri syndrome are grossly understudied, and investigation into whether these hormonal changes can trigger headache or even venous sinus stenosis would be particularly interesting.…”
Section: Discussionmentioning
confidence: 99%